Anti-beta 7 integrin treatment impedes the recruitment on non-classical monocytes to the gut and delays macrophage-mediated intestinal wound healing - Sommer, Katrin; Heidbreder, Karin; Kreiß, Lucas; Dedden, Mark; Paap, Eva-Maria; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Müller, Tanja; Atreya, Imke; Waldner, Maximilian; Schürmann, Sebastian; et al. (Clinical and Translational Medicine, 2023)
BackgroundClosing mucosal defects to reach mucosal healing is an important goal of therapy in inflammatory bowel disease (IBD). Among other cells, monocyte-derived macrophages are centrally involved in such intestinal wound healing. We had previously demonstrated that the anti-alpha 4 beta 7 integrin antibody vedolizumab blocks the recruitment of non-classical monocytes as biased progenitors of wound healing macrophages to the gut and delays wound healing. However, although important for the interpretation of disappointing results in recent phase III trials in IBD, the effects of the anti-beta 7 antibody etrolizumab on wound healing are unclear so far. MethodsWe analyzed the expression of etrolizumab targets on human and mouse monocyte subsets by flow cytometry and assessed their function in adhesion and homing assays. We explored wound-associated monocyte recruitment dynamics with multi-photon microscopy and compared the effects of etrolizumab and vedolizumab surrogate (-s) antibodies on experimental wound healing and wound-associated macrophage abundance. Finally, we investigated wound healing macrophage signatures in the large intestinal transcriptome of patients with Crohn's disease treated with etrolizumab. ResultsHuman and mouse non-classical monocytes expressed more alpha E beta 7 integrin than classical monocytes and were a target of etrolizumab-s, which blocked non-classical monocyte adhesion to MAdCAM-1 and E-Cadherin as well as gut homing in vivo. Intestinal wound healing was delayed on treatment with etrolizumab-s along with a reduction of peri-lesional wound healing macrophages. Wound healing macrophage signatures in the colon of patients with Crohn's disease were substantially down-regulated on treatment with etrolizumab, but not with placebo. ConclusionsCombined blockade of alpha E beta 7 and alpha 4 beta 7 with etrolizumab seems to exceed the effect of anti-alpha 4 beta 7 treatment on intestinal wound healing, which might help to inform further investigations to understand the recent observations in the etrolizumab phase III trial program.
CRIS-Team WoS Importer:2023-05-05

Discrepant Phenotyping of Monocytes Based on CX3CR1 and CCR2 Using Fluorescent Reporters and Antibodies - Sommer, Katrin; Garibagaoglu, Hilal; Paap, Eva-Maria; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Krönke, Gerhard; Neurath, Markus; Zundler, Sebastian (Cells, 2024)
Monocytes, as well as downstream macrophages and dendritic cells, are essential players in the immune system, fulfilling key roles in homeostasis as well as in inflammatory conditions. Conventionally, driven by studies on reporter models, mouse monocytes are categorized into a classical and a non-classical subset based on their inversely correlated surface expression of Ly6C/CCR2 and CX3CR1. Here, we aimed to challenge this concept by antibody staining and reporter mouse models. Therefore, we took advantage of Cx3cr1GFP and Ccr2RFP reporter mice, in which the respective gene was replaced by a fluorescent reporter protein gene. We analyzed the expression of CX3CR1 and CCR2 by flow cytometry using several validated fluorochrome-coupled antibodies and compared them with the reporter gene signal in these reporter mouse strains. Although we were able to validate the specificity of the fluorochrome-coupled flow cytometry antibodies, mouse Ly6Chigh classical and Ly6Clow non-classical monocytes showed no differences in CX3CR1 expression levels in the peripheral blood and spleen when stained with these antibodies. On the contrary, in Cx3cr1GFP reporter mice, we were able to reproduce the inverse correlation of the CX3CR1 reporter gene signal and Ly6C surface expression. Furthermore, differential CCR2 surface expression correlating with the expression of Ly6C was observed by antibody staining, but not in Ccr2RFP reporter mice. In conclusion, our data suggest that phenotyping strategies for mouse monocyte subsets should be carefully selected. In accordance with the literature, the suitability of CX3CR1 antibody staining is limited, whereas for CCR2, caution should be applied when using reporter mice.
CRIS-Team Scopus Importer:2024-05-31
Keywords: C-X3-C motif chemokine receptor 1 (CX3CR1); chemokine (C-C motif) receptor 2 (CCR2); classical monocytes; lymphocyte antigen 6C (Ly6C); non-classical monocytes

Intestinal Mucosal Wound Healing and Barrier Integrity in IBD–Crosstalk and Trafficking of Cellular Players - Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja; Heidbreder, Karin; Voskens, Caroline; Neurath, Markus; Zundler, Sebastian (Frontiers in Medicine, 2021)
The intestinal epithelial barrier is carrying out two major functions: restricting the entry of potentially harmful substances while on the other hand allowing the selective passage of nutrients. Thus, an intact epithelial barrier is vital to preserve the integrity of the host and to prevent development of disease. Vice versa, an impaired intestinal epithelial barrier function is a hallmark in the development and perpetuation of inflammatory bowel disease (IBD). Besides a multitude of genetic, molecular and cellular alterations predisposing for or driving barrier dysintegrity in IBD, the appearance of intestinal mucosal wounds is a characteristic event of intestinal inflammation apparently inducing breakdown of the intestinal epithelial barrier. Upon injury, the intestinal mucosa undergoes a wound healing process counteracting this breakdown, which is controlled by complex mechanisms such as epithelial restitution, proliferation and differentiation, but also immune cells like macrophages, granulocytes and lymphocytes. Consequently, the repair of mucosal wounds is dependent on a series of events including coordinated trafficking of immune cells to dedicated sites and complex interactions among the cellular players and other mediators involved. Therefore, a better understanding of the crosstalk between epithelial and immune cells as well as cell trafficking during intestinal wound repair is necessary for the development of improved future therapies. In this review, we summarize current concepts on intestinal mucosal wound healing introducing the main cellular mediators and their interplay as well as their trafficking characteristics, before finally discussing the clinical relevance and translational approaches to therapeutically target this process in a clinical setting.
CRIS-Team Scopus Importer:2021-04-16
Keywords: IBD; intestinal epithelial barrier function; intestinal epithelial cells; mucosal healing; wound healing

Nr4a1-dependent non-classical monocytes are important for macrophage-mediated wound healing in the large intestine - Heidbreder, Karin; Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Hildner, Kai; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2023)
Introduction: Macrophages play an important role in intestinal wound healing. However, the trajectories from circulating monocytes to gut macrophages are incompletely understood. Methods: Taking advantage of mice depleted for non-classical monocytes due to deficiency for the transcription factor Nr4a1, we addressed the relevance of non-classical monocytes for large intestinal wound healing using flow cytometry, in vivo wound healing assays and immunofluorescence. Results: We show that wound healing in Nr4a1-deficient mice is substantially delayed and associated with reduced peri-lesional presence of macrophages with a wound healing phenotype. Discussion: Our data suggest that non-classical monocytes are biased towards wound healing macrophages. These insights might help to understand, how targeting monocyte recruitment to the intestine can be used to modulate intestinal macrophage functions.
CRIS-Team Scopus Importer:2023-02-10
Keywords: gut homing; intestinal wound healing; macrophages; monocytes; Nr4a1 (Nur77)

Total Recall: Intestinal T-RM Cells in Health and Disease - Paap, Eva-Maria; Müller, Tanja; Sommer, Katrin; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2021)
Tissue-resident memory T cells (T-RM cells) have crucial functions in host defense in mucosal tissues. They provide local adaptive immune surveillance and allow the fast initiation of targeted adaptive immune responses in case of antigen re-exposure. Recently, an aberrant activation in the case of immunologically mediated diseases has been increasingly acknowledged. As the organ with the largest interface to the environment, the gastrointestinal tract faces billions of antigens every day. Tightly balanced processes are necessary to ensure tolerance towards non-hazardous antigens, but to set up a powerful immune response against potentially dangerous ones. In this complex nexus of immune cells and their mediators, T-RM cells play a central role and have been shown to promote both physiological and pathological events. In this review, we will summarize the current knowledge on the homeostatic functions of T-RM cells and delineate their implication in infection control in the gut. Moreover, we will outline their commitment in immune dysregulation in gastrointestinal chronic inflammatory conditions and shed light on T-RM cells as current and potential future therapeutic targets.
CRIS-Team WoS Importer:2021-02-19